Judy Moody Declares Independence! [anglicky] / Book 6. - McDonald, Megan 1959- (Walker Books Ltd, 2019)
When Judy meets Tori, an English girl, at the Boston "Tea Party" ship, she learns that Tori enjoys far more liberties than she does, including her own phone, private loo and lots of pocket money. So Judy decides to declare independence from her parents' rules and her pesky little "bother". But when staging her own Boston tea party doesn't work, she is forced into retreat ... until a real-life crisis gives Judy a chance to prove her independence, once and for all.